STRENGTHENING TRANSPARENCY AND ACCOUNTABILITY IN VILLAGE FUND MANAGEMENT THROUGH A FINANCIAL LAW APPROACH - Hendra Karianga (Faculty of Law, Universitas Pekalongan, 2023)
This study explores ways to make Village Funds management in Indonesia more open and responsible by using both financial law ideas and digital governance strategies in today's digital world. This study is important because there are still problems with managing village money, like not having enough trained people, weak internal controls, and constant corruption, even though there are more laws and digital tools like SISKEUDES being used. The purpose of this research is to see how legal rules fit with what is really happening, to judge how well digital systems make things more transparent, and to discover ways to encourage governance that is responsible and prevents corruption. The study uses a qualitative method that combines legal study with real-world research to look at important laws—like Law No. 6/2014, Minister of Home Affairs Regulation No. 20/2018, and Minister of Villages Regulation No. 6/2020—along with actual information gathered from observations and documents. The findings show that digital technology greatly improves how correct reports are, the tracking of audits, and the public's ability to see financial information, but its success depends on administrative skills, technology setup, and the regular enforcement of legal guidelines. It determines that to improve how Village Funds are governed, there needs to be a strong legal foundation, skill development, effective monitoring systems, and digital tools that encourage transparency, responsibility, and community involvement.